Undergraduate EFL Students’ Speaking Skill Development through Project-Based Learning: Experiences and Challenges - Khofifah, Siti; Maulidiyah, Noor (Proceeding International Conference on Education, 2025)
Speaking competence plays a vital role in English language learning; however, many EFL undergraduates still struggle to develop it effectively. This study aims to examine the experiences and challenges of undergraduate EFL students in enhancing their speaking skills through the Project-Based Learning approach. Employing a qualitative narrative inquiry design, data were obtained through in-depth interviews with ten English Education students at UIN Antasari Banjarmasin who participated in a podcast-based project. The results indicate that PjBL contributes positively to students’ speaking performance, particularly in vocabulary development, pronunciation accuracy, fluency, and self-confidence. It also fosters higher motivation and active participation in learning. Nevertheless, several challenges were identified, including teamwork issues, anxiety in public speaking, and topic selection difficulties. The study concludes that PjBL is an effective strategy for promoting speaking skill development, provided that lecturers offer consistent guidance and build a supportive learning environment.